Educational design research. - Van den Akker, Jan, ....-; Gravemeijer, Koeno, ....-; McKenny, Susan, ....- (London : Routledge, 2006)
The field of design research has been gaining momentum over the last five years, particularly in educational studies. As papers and articles have grown in number, definition of the domain is now beginning to standardise. This book fulfils a growing need by providing a synthesised assessment of the use of development research in education. It looks at four main elements: > background information including origins, definitions of development research, description of applications and benefits and risks associated with studies of this kind > how the approach can serve the design of learning environments and educational technology > quality assurance - how to safeguard academic rigor while conducting design and development studies > a synthesis and overview of the topic along with relevant reflections. Contents Part 1: What and Why Introducing Educational Design Research Toward Productive Design Studies Part 2: Examples from the Field Design research from the Learning Design Perspective Design Research from the Technology Perspective Design Research from a Curriculum Perspective Part 3: Quality Assessing the Quality of Design Research Proposals: Some Philosophical Perspectives Balancing Innovation and Risk: Assessing Design Research Proposals Quality Criteria for Design Research: Evidence and Commitments Part 4: Moving ahead From Design Research to Large-Scale Impact: Engineering Research in Education Educational Design Research: The Value of Variety
Keywords: Onderwijsonderzoek